2001
DOI: 10.1086/320181
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Prevalence of Antimicrobial Resistance inStreptococcus pneumoniae, Haemophilus influenzae,andMoraxella catarrhalisin the SENTRY Antimicrobial Surveillance Program, 1997–1999

Abstract: The in vitro activities of numerous antimicrobials against clinical isolates of Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis from patients with bloodstream and respiratory tract infections in the United States, Canada, Europe, Latin America, and the Asia-Pacific region were studied in the SENTRY Antimicrobial Surveillance Program. Penicillin resistance (minimum inhibitory concentration, > or =2 microg/mL) was noted in all 5 geographic regions, and a high and increasing rate of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
214
2
19

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(258 citation statements)
references
References 39 publications
(64 reference statements)
23
214
2
19
Order By: Relevance
“…These concentrations are well above the minimum inhibitory concentrations (MICs) of the majority isolates of the 3 most common otitis pathogens: Streptococcus pneumoniae (MIC 50 , 0.06 µg/mL; MIC 90 , 16 µg/mL; 72.3% susceptible), Haemophilus influenzae (MIC 90 , 2 µg/mL; 99.5% susceptible), and Moraxella catarrhalis (MIC 90 , Յ0.12 µg/mL; 99.9% susceptible). 29,30 Dagan et al 31 also determined middle-ear fluid levels of azithromycin in children with AOM who received the 3-day regimen. They reported a total mean azithromycin concentration of 3.51 µg/mL at 24-48 hours after the last dose.…”
Section: A17mentioning
confidence: 99%
“…These concentrations are well above the minimum inhibitory concentrations (MICs) of the majority isolates of the 3 most common otitis pathogens: Streptococcus pneumoniae (MIC 50 , 0.06 µg/mL; MIC 90 , 16 µg/mL; 72.3% susceptible), Haemophilus influenzae (MIC 90 , 2 µg/mL; 99.5% susceptible), and Moraxella catarrhalis (MIC 90 , Յ0.12 µg/mL; 99.9% susceptible). 29,30 Dagan et al 31 also determined middle-ear fluid levels of azithromycin in children with AOM who received the 3-day regimen. They reported a total mean azithromycin concentration of 3.51 µg/mL at 24-48 hours after the last dose.…”
Section: A17mentioning
confidence: 99%
“…The prevalence of S. pneumoniae strains resistant to β -lactams has increased around the world since the 1980s (Hoban et al 2001;Örtqvist et al 2005;File 2006). In Japan, several studies have shown an increasing prevalence of β -lactam-and macrolide-resistant strains (Rikitomi et al 1996;Song et al 1999;Watanabe et al 2000;Ubukata 2003;Ubukata et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of greater concern is the emergence of a multidrug-resistant phenotype (i.e., resistant to penicillin and ≥ 2 other non-β -lactam classes, such as macrolides and tetracyclines). Certain β -lactams (ceftriaxone, carbapenem), the respiratory fluoroquinolones and telithromycin are among several antimicrobials that remain effective against drug-resistant S. pneumoniae (Hoban et al 2001;Örtqvist et al 2005;File 2006). Initial antibacterial therapy should ideally be pathogen-directed, based on culture results and antibacterial sensitivity tests.…”
mentioning
confidence: 99%
“…More than 50% of isolates now found in several countries are resistant to penicillin (1,7,13,14,25), with Spain as one of the countries with the highest penicillin resistance rates (18). Among penicillin-resistant S. pneumoniae isolates, 60 to 80% are also resistant to cefuroxime, erythromycin, and clindamycin (13).…”
mentioning
confidence: 99%